The Walking Muse : Horace on the Theory of Satire - Freudenburg, Kirk, 1961- (Book collections on Project MUSE., 1993)
In laying the groundwork for a fresh and challenging reading of Roman satire, Kirk Freudenburg explores the literary precedents behind the situations and characters created by Horace, one of Rome's earliest and most influential satirists. Critics tend to think that his two books of Satires are but trite sermons of moral reform--which the poems superficially claim to be--and that the reformer speaking to us is the young Horace, a naive Roman imitator of the rustic, self-made Greek philosopher Bion. By examining Horace's debt to popular comedy and to the conventions of Hellenistic moral literature, however, Freudenburg reveals the sophisticated mask through which the writer distances himself from the speaker in these earthy diatribes--a mask that enables the lofty muse of poetry to walk in satire's mundane world of adulterous lovers and quarrelsome neighbors. After presenting the speaker of the diatribes as a stage character, a version of the haranguing cynic of comedy and mime, Freudenburg explains the theoretical importance of such conventions in satire at large. His analysis includes a reinterpretation of Horace's criticisms of Lucilius, and ends with a theory of satire based on the several images of the satirist presented in Book One, which reveals the true depth of Horace's ethical and philosophical concerns. Originally published in 1992. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.